Penerapan Material Bahan Bangunan dan Konsep Pemaknaan pada Gereja Puh Sarang sebagai Warisan Budaya Indonesia - Grace Hartanti (Humaniora, 2011)
Puh Sarang Church which located at Kediri, East Java, Indonesia, who’s made by Henri Maclaine Pont, give an illustrated of case study, how the Church developed with a good and great idea from the Architect which his effort to revitalized a local mind (intelligence) and then to transformed in a new form (modern form), but it is still hold on a local paradigm. The Puh Sarang Church in Kediri is different with any church form that build in Java (in that time) which some Church architecture and interior design a propose from Europe. Besides make use of local potency, Puh Sarang Church shown the impression of a sustainable product, because all of the transformation which Henri Maclaine Pont has already happens, he still use the natural paradigm became prime element for the design and the development. The aim of this paper is want to show if the architectural and interior design’s product done with use local paradigm in the concept, design, and carried by material, new technology is effort revitalization and transformation architecture and interior design as a holistic and comprehensive thinking.